Heat transfer and flow characteristics of conventional fluids and nanofluids in curved tubes: A review. (May 2016) - Huminic, Gabriela; Huminic, Angel
Abstract: The purpose of this review summarizes the recent published papers on the heat transfer and fluid flow characteristics in curved tubes using conventional fluids and nanofluids as working fluids. The use of the nanofluids in curved tubes has been investigated in recent years by various researchers for finding new opportunities of enhancement of the thermo-hydrodynamical performances. The curved tubes were divided into three groups: helically coiled tubes, spirally coiled tubes and other curved tubes, according with configurations of the tube curvature. The paper presents experimental, numerical and analytical published studies in literature.